(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация: Статья посвящена актуальной проблеме формирования межкультурной коммуникативной компетенции у учащихся академических лицеев Узбекистана в процессе обучения английскому языку. В работе рассматриваются теоретические основы межкультурной коммуникации, анализируются методы и приемы ее развития в рамках учебного процесса. Особое внимание уделяется использованию аутентичных материалов, организации межкультурных проектов и ролевых игр. Автор подчеркивает важность развития у учащихся не только языковых навыков, но и способности понимать и уважать другие культуры. Abstract: This article addresses the pressing issue of developing intercultural communicative competence among academic lyceum students in Uzbekistan through English language teaching. The paper examines the theoretical foundations of intercultural communication and analyzes methods and techniques for its development within the educational process. Particular attention is paid to the use of authentic materials, the organization of intercultural projects, and role-playing games. The author emphasizes the importance of developing not only language skills but also the ability to understand and respect other cultures in students.